Lipid metabolism in Decapods: transcripts of relevant enzymes - Koch, Marie; Tebben, Jan; Saborowski, Reinhard (In: Koch, M et al. (2023): Lipid metabolism in Decapods: DGAT activity, total lipid content, transcripts of relevant enzymes [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955471, 2023)
Transcripts of relevant enzymes of the storage lipid metabolism were obtained from already existing transcriptomes that are available in the NCBI database (https://blast.ncbi.nlm.nih.gov/Blast.cgi). Transcriptomes originate from pooled midgut gland samples of several individuals cought in the North Sea. The transcriptome of Crangon crangon is found in the BioProject PRJNA479562 and of Pandalus montagui under BioProject PRJNA798226. Transcripts identified as relevant enzymes are noted by their Trinity_ID and identified through Blastn and Blastp. The nucleotide sequences were translated into amino acid sequences wih the largest ORF. More information about each of the transcriptomes is provided under the individual BioProjects.
Keywords: enzyme activity; Lipid; Transcriptomics